Compressive strength of oil palm shell lightweight aggregate concrete containing clinker as sand replacement - Muhammad Nazrin Akmal, Ahmad Zawawi; Khairunisa, Muthusamy; Nasly, Mohd Ali (Universiti Malaysia Pahang, 2016)
Annually, huge quantity of solid wastes namely oil palm shell and clinker from Malaysian palm oil mills were disposed as waste at dumping site. Continuous dumping of waste which has been increases over the years causes more land to be used for waste disposal and also cause pollution to the environment. Realizing that utilization of these waste material in concrete production would reduce amount of waste disposed, efforts has been taken to integrate both oil palm shell and clinker as mixing ingredient to produce palm oil waste lightweight aggregate concrete. The present research was conducted to investigate the effect of palm oil clinker as sand replacement towards workability, density and compressive strength of oil palm shell lightweight aggregate concrete. All the specimens were prepared in form of cubes and water cured until the testing age. The compressive strength test was carried out at 7 and 28 days. The result shows that inclusion of suitable amount of palm oil clinker as sand replacement would be able to produce a more environmental friendly oil palm shell lightweight aggregate concrete suitable for structural application. Incorporation of palm oil clinker as mixing ingredient would reduce the amount of clinker disposed as waste and also control the use of natural river sand mined from the river bed thus ensuring ecological balance as well as cleaner environment for future generation.